An international multidisciplinary consensus statement on fasting before procedural sedation in adults and children. (2nd December 2019) - Green, S. M.; Leroy, P. L.; Roback, M. G.; Irwin, M. G.; Andolfatto, G.; Babl, F. E.; Barbi, E.; Costa, L. R.; Absalom, A.; Carlson, D. W.; Krauss, B. S.; Roelofse, J.; et al.
Summary: The multidisciplinary International Committee for the Advancement of Procedural Sedation presents the first fasting and aspiration prevention recommendations specific to procedural sedation, based on an extensive review of the literature. These were developed using Delphi methodology and assessment of the robustness of the available evidence. The literature evidence is clear that fasting, as currently practiced, often substantially exceeds recommended time thresholds and has known adverse consequences, for example, irritability, dehydration and hypoglycaemia. Fasting does not guarantee an empty stomach, and there is no observed association between aspiration and compliance with common fasting guidelines. The probability of clinically important aspiration during procedural sedation is negligible. In the post‐1984 literature there are no published reports of aspiration‐associated mortality in children, no reports of death in healthy adults (ASA physical status 1 or 2) and just nine reported deaths in adults of ASA physical status 3 or above. Current concerns about aspiration are out of proportion to the actual risk. Given the lower observed frequency of aspiration and mortality than during general anaesthesia, and the theoretical basis for assuming a lesser risk, fasting strategies in procedural sedation can reasonably be less restrictive. We present a consensus‐derived algorithm in which each patient is first risk‐stratified during their pre‐sedation assessment, using evidence‐based factors relating to patient characteristics, comorbidities, the nature of the procedure and the nature of the anticipated sedation technique. Graded fasting precautions for liquids and solids are then recommended for elective procedures based upon this categorisation of negligible, mild or moderate aspiration risk. This consensus statement can serve as a resource to practitioners and policymakers who perform and oversee procedural sedation in patients of all ages, worldwide.